Analysis Study of the Gaps in Elementary School Personnel Components in Implementing Child-Friendly School Programs - Apriyanto, Ridwan Eko; Suszanty, Nila Trisna Widya; Khamid, Muh; Jabar, Cepi Safruddin Abdul (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2024)
Elementary school is one of the levels of education in Indonesia where there are quite a lot of cases of bullying/violence within the school environment. The government has attempted to prevent bullying in schools by declaring child-friendly schools. Various efforts have been made by schools so that program implementation can take place as expected. In practice, however, quite a few schools experience irregularities in implementing the programs. This research aims to analyze aspects of elementary school personnel in implementing child-friendly school programs. The research method used in this study is qualitative, with the type of study being a case study. Various data collection techniques, such as interviews, observation, and document analysis, are used. The program has several data sources, including school personnel and relevant documents. Analyzing data involves reducing and searching for subthemes and relationships between subthemes. The research results show a gap in school personnel implementing child-friendly school programs. Some problems exist, including unequal training for school personnel, no workgroup program, and no accompanying counseling staff. It was concluded that implementing child-friendly school programs still requires further improvement and development, especially concerning school personnel.